Clasificación de competencias investigativas en la educación superior - Ochoa Jaramillo, Jhon (2025)
Research competences play a crucial role in the scientific academy, which has led to diverse interpretations and classifications by researchers, with few common agreements. For this reason, the objective of this article is to offer a classification of research competencies that considers knowledge, skills, values and attitudes, encompassing knowledge, know-how and know-how to be, in the field of higher education, especially in Latin America. In order to develop this synthesis, a documentary review based on reliable sources of the last five years was carried out. The results revealed that most classifications consider communicative and methodological competencies, and that ethical competencies include values, aptitudes and attitudes, and cognitive-practical competencies include knowledge, mental and procedural processes.